PENGARUH PENERAPAN KURIKULUM MERDEKA DALAM PENINGKATAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM KELAS X SMA DARUL ULUM SUGIO LAMONGAN - Rokim; Zakariyah; Yulianto; Ach. Romli (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study explores the impact of implementing the independent curriculum on the motivation to learn Islamic education among Class X students at SMA Darul Ulum Medali Sugio Lamongan. The research aims to: (1) examine the implementation of the independent curriculum at SMA Darul Ulum Sugio Lamongan, (2) investigate the improvement in students' motivation to learn Islamic education, and (3) determine whether the implementation of the independent curriculum influences students' motivation. Employing a quantitative research method with a descriptive quantitative research design, the findings indicate: (1) The implementation of the independent curriculum at SMA Darul Ulum Sugio Lamongan is effective, with a percentage value of 71.3%. (2)The improvement in motivation to learn Islamic education in Class X is considered sufficient, with a percentage value of 69.8%. (3) A simple linear regression analysis using SPSS confirms that the implementation of the independent curriculum significantly influences students' motivation to learn Islamic education. The significance value of 0.003 confirms statistical significance; however, the calculated t-value of 0.302 is lower than the t-table value of 1.986, indicating a negative impact. These findings suggest that while the independent curriculum implementation significantly affects students' motivation, further research is necessary to understand potential challenges or limitations within its execution.